Microplastics contamination in aquaculture-rich regions: a case study in Gresik, East Java, Indonesia - Anjeli, Ulfa Gita (2024)
The widespread use of plastic has resulted in the accumulation of plastic waste across a range of sizes, notably including microplastics (MPs). The introduction of MPs into aquatic ecosystems can lead to the contamination of organisms, mainly fish. This study reports for the first time a quantitative and qualitative analysis conducted on the abundance of MPs encountered in water and sediment of milkfish aquaculture ponds in Gresik, East Java, Indonesia. Water and sediment samples were collected at three stations between February to April 2021. The abundance of MPs was analyzed through the application of one-way ANOVA tests and Pearson's correlation analysis. The results identified four types of MPs: fragments, fibers, films, and pellets. The highest abundance of MPs in both water (10.40 particle/L) and sediment samples (1.15 particle/g) was observed in March. The predominant MPs size in the water samples is 100-500 μm, while it is below 100 μm in the sediment. The color of the MPs varied across eight colors: black, purple, red, blue, yellow, pink, green, and transparent. The identification of MPs polymers was found to be polypropylene (PP), Polyurethane (PU), Polycarbonate (PC), Polyethylene terephthalate (PETE), High-density polyethylene (HDPE), and low-density polyethylene (LDPE). The presence of MPs in the water column and sediments was correlated with human activities around the ponds. Hence, the abundance of MPs is a source of pollution that has the potential to damage the nutritional quality of farmed milkfish. This study provides important information for the local governments to develop waste management policies for a cleaner environment and improved human health.